Peran Forum Koordinasi Pencegahan Terorisme dalam Menjalankan Program Deradikalisasi - Rapik, Mohamad; Permatasari, Bunga; Anisya, Adinda Farah (Journal of Political Issues, 2020)
This article aims to elaborate an empirical study on the role of the FKPT (Coordintaing Forum on The Eradication of Terrorism). This article is based on an assummtion that the FKPT is a vital agent hoped to play a significant role of dradicalisation. The study was conducted to proof as to wether this assumtion is right or wrong by observing the performaance of this agent. In addition to study of its performance, the article also focuses on the issue of deradicalisation on the assumtion that it is program that the FKPT should play its role. Any affort to eradicate terrorism should only be efficient through a work of deradicalisation. The essence of this program is to shift paradigm or mindset which is believed to have been dangerous and misleading. Applying an empitical legal approach, this study aims to explore deeply the application of the deradicalisation and its influence in enhanching community awareness against the danger of terrorism. It is found through this study that the FKPT, as long as its role is concerned, has been working so efficently by advocating brokers to dessimanate its mission of deradicalisation. However, the study also revealed waknessess during its program showing that the community awareness over the danger of the terrorism ideology has not increasingly shifted as the program might have expected. Istead, as the study revealed, religious extremism seems to have been increased lately. It is suggested through this study that the FKPT work more expansively reaching the root, especially to the lay people and students as they have mostly been the main target of radicalisation and of potentially terrorism.